Leveraging Digital Tools for Improving Speaking Skills among Undergraduate Students - Shabreen Sultana Shaik (MultiTech Publisher, 2025)
In the contemporary landscape of English Language Teaching (ELT), digital resources have emerged as powerful tools for enhancing language proficiency. The development of speaking skills, in particular, has seen significant advancements due to technological innovations. This paper investigates the efficacy of leveraging digital tools to enhance speaking skills among undergraduate students. The integration of digital resources has revolutionized traditional pedagogical methods, offering interactive and engaging platforms for language practice. This study delves into the types of digital tools available, their classroom implementation, and the perceptions of students and educators regarding their effectiveness. Through a mixed-methods approach involving pre- and post-tests, surveys, and interviews, the research analyzes the impact of digital tools on speaking proficiency. Key findings indicate significant improvements in speaking abilities, with tools like Duolingo, Italki, and Zoom facilitating enhanced feedback, engagement, and interaction. While acknowledging challenges such as technical issues and the need for comprehensive training, the study emphasizes the transformative potential of digital resources in ELT, providing valuable insights for optimizing language learning outcomes.